Strengths-based Gram Sabhas? Challenges and radical possibilities when 'measuring' poverty in India. - Sekher, Madhushree; Hodge, Paul; Aulakh, Balbir Singh (Third World Quarterly, 2023)
Poverty as an object of study in India continues to be the domain of economists, statisticians and demographers. The National Sample Survey Organisation (NSS) serves as the main instrument of data collection to measure poverty relative to economic indicators. In this paper we draw on strengths-based research undertaken in an Indian village to foreground alternative ways of conceptualising and practising data collection when measuring poverty. Explored through an analytics of biopolitics, asset-mapping exercises with young people and women revealed new subjectivities that emerged via illustrative meaning-making and dialogue. This approach to poverty measurement facilitated methods and produced outcomes that were less calculated and predefined than the NSS, and encouraged participation, even questioning of the status quo, in the 'doing' of the methodology itself. A strengths orientation to poverty opens up radical possibilities, particularly in India where the state-sanctioned self--governing body, the Gram Sabhas, has a mandate to provide for the most marginalised groups. And while this governing body is not free from power imbalances, the potential it offers, when combined with strengths-based approaches (SBA) that value people for the expertise they already have, demands renewed attention in practitioner and policy debates in the country.